Pengaruh Dosis Bokashi Azolla Dan Beberapa Jenis Mulsa Terhadap Pertumbuhan Dan Hasil Tanaman Bawang Daun (Allium Fistulosum L.) - Susylowati Susylawati (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2015)
The aims of this research were to know the effect of fermented Azolla dosage and mulch types on the growth and yield of leeks, and the optimum dosage of fermented Azolla to the yield. This experiment was conducted from August to September 2013, at Jalan Panjaitan, Temindung Permai, Samarinda Utara. The experiment design was Randomized Blok Design (RBD) and three replication. The first factor was fermented bokashi dosage wich consisted of four levels 0, 4, 8, 12 Mg ha-1. The second factor was mulch types without mulch, plastic mulch, and rice straw mulch. The result of the research showed that treatment of fermented Azolla concentration were not significant difference from the average of plant height addition, the average of number of leaves, the average number of the average of fresh weight per plot, but significant difference from the average of fresh weight per hectare and the dry weight. The best dosage that produced the highest fresh weight (2.938 Mg ha-1) was 12 Mg ha-1 fermented Azolla. The mulch types treatment was not significant difference from the average of plant height addition the average number of leaves at 15 Days After Planting (DAP) and the average number of tillers per clumps. Significant difference from the average number of leaf 30, 45 Days After Planting (DAP), and at harvest times, the average of fresh weight per plant, the average of fresh weight per plot, the average of fresh weight per hectare and the average of dry weight per plant. The best mulch that produced the highest folsh weight (3.069 Mg ha-1) was rice straw mulch. According to analysis of variance showed that interaction between fermented Azolla dosage and mulch types was not significant difference from all variables was observed.